Heterogeneity of opinion, shareholder retention ratio and lockup period: Malaysian evidence - Albada, Ali; Low, Soo Wah; Yong, Othman; Md Nassir, Annuar; Kamarudin, Fakarudin; Mohamad Anwar, Nazratul Aina (Fakulti Ekonomi dan Pengurusan, Universiti Putra Malaysia, 2019)
This paper examines the effects of the lock-up period and shareholder retention ratio on the heterogeneity of investors beliefs regarding the true value of IPOs in the Malaysian IPO market. The relationship between the signalling variables and the first-day price range of IPOs is examined using a quantile regression (QR) technique. This study employs a sample of 377 IPOs issued between January 2000 and December 2015. The results show that shareholder retention ratio has a significant negative relationship with the first-day price range, while the lock-up period does not have a significant relationship with the first-day price range. This suggests that prospective investors acknowledge the importance of the shareholder retention ratio as a signal and use the information conveyed by this signal to evaluate the price of the listing firm’s IPO and to ensure that the current price reflects their beliefs and expectations of the firm in general and the issue price in particular. Finally, the lock-up in the Malaysian market serves as precautionary measure to guard the investors against after-market insiders’ actions.